2020
DOI: 10.1186/s12891-020-03549-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel transplant of combined platelet-rich fibrin Releasate and bone marrow stem cells prevent bone loss in Ovariectomized osteoporotic mice

Abstract: Background: Osteoporosis is a metabolic bone disorder characterized by deterioration in the quantity and quality of bone tissue, with a consequent increase susceptibility to fracture. Methods: In this study, we sought to determine the efficacy of platelet-rich fibrin releasates (PRFr) in augmenting the therapeutic effects of stem cell-based therapy in treating osteoporotic bone disorder. An osteoporosis mouse model was established through bilateral ovariectomy on 12-week-old female ICR (Institute of Cancer Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Several studies have demonstrated the effectiveness of platelet concentrates for the treatment and management of osteoporosis (Tables 2 and 3 ) [ 21 23 , 37 , 56 64 ]. All studies were conducted on ovariectomized (OVX) animal models including mice [ 22 , 23 , 37 , 56 ], rats [ 21 , 57 60 , 62 , 64 ], and rabbits [ 61 , 63 ]. In these studies, the systemic and localized application of platelet concentrates (PRP or PRF) alone or in combination with osteoinductive and osteoconductive biomaterials has been investigated [ 21 , 37 , 57 , 58 , 60 64 ].…”
Section: Role Of Pdbs In Osteoporosismentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have demonstrated the effectiveness of platelet concentrates for the treatment and management of osteoporosis (Tables 2 and 3 ) [ 21 23 , 37 , 56 64 ]. All studies were conducted on ovariectomized (OVX) animal models including mice [ 22 , 23 , 37 , 56 ], rats [ 21 , 57 60 , 62 , 64 ], and rabbits [ 61 , 63 ]. In these studies, the systemic and localized application of platelet concentrates (PRP or PRF) alone or in combination with osteoinductive and osteoconductive biomaterials has been investigated [ 21 , 37 , 57 , 58 , 60 64 ].…”
Section: Role Of Pdbs In Osteoporosismentioning
confidence: 99%
“…Thus, the authors [ 23 ] concluded that the combined application of ADSCs and PRFr was the most optimized treatment for the healing of bone defects in these osteoporotic animals. In another study by Wong et al [ 22 ], PRFr was used in conjunction with bone marrow stem cells (BMSCs) and intravenously injected either once only or once a week for 4 consecutive weeks during the 8 week study period. PRFr alone and BMSCs alone were utilized as controls.…”
Section: Role Of Pdbs In Osteoporosismentioning
confidence: 99%
See 3 more Smart Citations